Phytochemical profiling and anti-Staphylococcus epidermidis activity of mango leaf extract using gas chromatography-mass spectrometry - Waluyo, Joko; Kuswati, Kuswati; Putri, Rizqi Wulandari; Rosalinda, Julitha D; Fatmawati, Yayuk; Habibi, Mohammad Wildan (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Staphylococcus epidermidis is increasingly recognized for its resistance to certain antibiotics, posing a significant threat due to its potential to cause infections. Plant extracts have emerged as promising alternatives owing to their diverse phytochemical composition. This study aimed to evaluate the antibacterial efficacy of the ethanolic extract of Arumanis mango leaves (Mangifera indica L. var. arumanis) against S. epidermidis and to characterize its metabolite profile using Gas Chromatography-Mass Spectrometry (GC-MS). Employing the disc diffusion method, the extract demonstrated inhibitory activity against S. epidermidis at a concentration of 2% (2 mg/ml). Subsequent GC-MS analysis identified phenols, flavonoids, and alcohols as the predominant bioactive compounds, consistent with their known antibacterial properties. These findings suggest that Arumanis mango leaf extract holds potential as a natural antibacterial agent against S. epidermidis and warrants further investigation for incorporation into natural antibacterial formulations.